1989
DOI: 10.1111/j.1432-1033.1989.tb14844.x
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglycerol synthesis in cultured rat hepatocytes

Abstract: The limiting role of diacylglycerol acyltransferase with respect to triacylglycerol synthesis in cultured rat hepatocytes was evaluated by following the inhibition of the overall synthetic flux by 2-bromooctanoate acting as an inhibitor of the diacylglycerol acyltransferase step. The flux-control coefficient of diacylglycerol acyltransferase in intact cultured hepatocytes amounted to 0.76 in the presence of saturating glycerol and either palmitate or oleate as the fatty acyl substrates. The flux-control coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 37 publications
(12 reference statements)
4
33
0
Order By: Relevance
“…The lower affinity of DGAT for acyl-CoA as compared with other enzymes in the FA esterification pathway (Fig. 5) has been suggested from results of enzymatic assays in intact and permeabilized hepatocytes (42,43). However, the findings presented here mark the first demonstration of a key regulatory role for DGAT in vivo and point to the pivotal role of membrane FA transport in maintaining acyl-CoA at the levels required for optimal DGAT activity.…”
Section: Discussionsupporting
confidence: 57%
“…The lower affinity of DGAT for acyl-CoA as compared with other enzymes in the FA esterification pathway (Fig. 5) has been suggested from results of enzymatic assays in intact and permeabilized hepatocytes (42,43). However, the findings presented here mark the first demonstration of a key regulatory role for DGAT in vivo and point to the pivotal role of membrane FA transport in maintaining acyl-CoA at the levels required for optimal DGAT activity.…”
Section: Discussionsupporting
confidence: 57%
“…DGAT is the terminal and only committed enzyme that catalyzes the acylation of DAG in the synthesis of TGs (25)(26)(27)(28). However, DAG used in the DGAT reaction can be derived from multiple pathways, including 1) hydrolysis of phosphatidic acid produced by the de novo synthesis pathway from glycerol-3-phosphate catalyzed by glycerol-3-phosphate acyltransferase; 2) esterification of monoacylglycerol catalyzed by MGAT; and 3) hydrolysis of TG or phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies with both mammalian (Mayorek et al, 1989;Tijburg et al, 1989) and plant (Ichihara et al, 1988;Harwood, 1993a, 1993b;Settlage et al, 1995;Perry et al, 1999) systems have suggested that DGAT may catalyze a rate-limiting reaction in TAG bioassembly. For example, developing seeds of B. napus L., cv Shiralee, have been shown to produce significant levels of DAG during the active phase of oil accumulation Harwood, 1993a, 1993b).…”
mentioning
confidence: 99%